A new control strategy for cutting force disturbance compensation for XY table ball screw driven system - Abdullah, Lokman (2014)
High tracking accuracy, precision and robustness are three vital components demanded in controller design for machining processes in many manufacturing related activities. This recent requirements or paradigm shift has led to a new and challenging era in the area of machining tools and control. However, the presence of disturbances during machining processes in the form of friction forces and cutting forces have greatly reduced positioning and tracking accuracy of the system. The objective of this thesis is to propose, design, develop and validate a new control strategy to further compensate effects of cutting forces on the positioning accuracy of a XY table ball screw driven system by Googoltech Inc. Issues pertaining to cutting force effects on machining process have been explored comprehensively in the past where various techniques and thoughts were introduced and validated. Conventional linear feedback control approach such as PI, PID or cascade control alone are inadequate to totally compensate the cutting force disturbance. This is due to the absence of adaptive element in the control scheme. Adaptive element is essential to solve the issue of nonlinearity of cutting force disturbance. This thesis proposes a new approach to compensate multiple frequency components of cutting forces, named Nonlinear Cascade Feedforward (NCasFF) controller. This new approach combined and embedded a modified nonlinear function, an inverse plant model feedforward and a speed feedforward onto the Cascade P/PI controller that serves as the primary position controller to further reduced the tracking error. The performance of the proposed controller was validated numerically and experimentally where actual machining process was performed on the test setup. The results indicated that the Nonlinear Cascade Feedforward (NCasFF) controller is able to compensate tracking errors introduced by the cutting forces. This thesis has successfully demonstrated that the tracking performance of a machine tool was increased significantly by the addition of dedicated compensation elements that supplement the classical Cascade P/PI position controller. Results showed that the newly proposed NCasFF control strategy manage to provide 33.80 % improved performance in terms of Root Mean Square Error (RMSE) reduction than Cascade P/PI controller and 16.03 % better performance in terms of Fast Fourier Transform (FFT) error than Cascade P/PI controller. Finally, in terms of surface roughness, Ra value, NCasFF controller provide 20 % improved performance than Cascade P/PI controller. However, further studies and improvement are desired. The performance of the controller needs to be further enhanced so that it can adapt to different conditions of cutting force disturbance. The improvement includes addition of adaptive elements to the controller to compensate changing cutting force characteristics and variable disturbance friction force resulting from different cutting conditions. For example, changes in tools diameter, tracking speed and depth of cut.